Effect of age and body weight on scrotal circumference and testicular growth in Nagaland swamp buffalo bulls - PERUMAL, P (The Indian Journal of Animal Sciences, 2018)
A study was carried out to assess the effect of age and body weight on the scrotal circumference (SC) and testicular growth rate of swamp buffalo bulls in Nagaland. These buffaloes utilized for the present study were maintained around the villages of Medziphema block, Dimapur district, Nagaland, India. In the present study, a total of 24 swamp buffalo bulls were identified, selected and utilized. These buffaloes were grouped into four different categories as per their age and each category comprised 8 buffalo bulls. The groups were Group I: 18-24 months (6), Group II: 25-36 months (6), Group III: 37-48 months (6) and Group IV: 49 months and above (6). SCand testicular growth parameters were estimated with vernier caliper and simple measurement tape and by using dental formula, the age of animals was estimated.The Shaeffer’s formula was used to estimate the body weight of buffalo bulls. Statistical analysis revealed that the SC and testicular growth parameters had significant positive correlation with body weight than age of the bulls. As compared to cattle, testicular growth parameters and SC of the swamp buffaloes were lower. The study result indicated that testicular growth parameters and SC of swamp buffalo are the useful indicators to determine the testicular development to select the buffalo bull for breeding purpose.